The Effectiveness of Breast Self-Examination Health Education (BSE) using Demonstrations and Lectures on The Level of Knowledge and Attitudes of Young Women - Kumala, Ratna Nur; Ruspita, Mimi; Ulfiana, Elisa (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2024)
Breast Self-Examination (BSE) is one of the easiest ways to detect breast cancer, but women’s awareness of doing BSE is still very low. Breast Cancer patients with advanced stages, an estimated 70% visit a health facility. The purpose of this study was to determine the differences in the level of knowledge and attitudes of adolescent girls in providing BSE health education with demonstration and lecture methods. This research was conducted at SMA Negeri 1 Driyorejo, Gresik. This research method is Quasi Experiment with Non Equivalent Control Group One Group Pretest-Posttest research design. The sampling technique uses Probability Sampling with Stratified Random Sampling. Data analysis used the Wilcoxon test.The results showed that there was an influence on the level of knowledge and attitudes of young women before and after being given BSE health education with the demonstration method with a p-value of 0.001 < (0.05), there was an influence on the level of knowledge and attitudes of young women before and after being given BSE health education. with the lecture method with a p-value of 0.001 < (0.05), there is a significant difference in the level of knowledge of young women in the provision of BSE health education with demonstration and lecture methods with a p-value of 0.015 < (0.05) and there is no significant difference the attitude of young women in providing BSE health education with demonstration and lecture methods with a p-value of 0.491 > 0.05. From the results of this study, it is hoped that students will be able to do BSE regularly and correctly in accordance with the 6 steps of BSE as an early detection of breast cancer, and the school will apply lecture and demonstration methods in teaching and learning activities.